Factors that influence pa of adult inhabitants in the Olomouc region - Svatopluk Horák; Jan Dygrýn; Josef Mitáš; Kateřina Obzinová (Palacký University Olomouc, 2011)
BACKGROUND: Regular physical activity has significant benefits for health. For instance, it can reduce the risk of cardiovascular disease, diabetes and osteoporosis, help control weight, and promote psychological well-being. There are many factors that can influence physical activity; socioeconomic status, family, size of place of residence, environmental conditions etc AIM: The aim of the study was to analyze physical activity and inactivity of adult population in the Olomouc region in terms of size of residence, type of housing, body weight status, smoking and participation in organized physical activity. METHODS: 1011 randomly selected residents of the Olomouc region (448 males and 563 females) aged 41.14 ± 8.63 years participated in this study. To obtain selected indicators of physical activity, we used the ANEWS questionnaire which was distributed by university students in Spring and Fall periods from 2005 to 2009. For healthy adults aged 18 to 65 years, the goal recommended by the WHO is to achieve a minimum of 30 minutes of moderateintensity physical activity 5 days a week or at least 20 minutes of vigorous-intensity physical activity 3 days a week. RESULTS: The most physically active were males aged 36-45 years. From the selected correlates, those with the highest influence on total weekly PA were the size of residence and type of house. On the other hand, factors that did not affect total weekly PA were smoking, participation in organized PA and body mass index. The most commonly performed type of PA is cycling; followed in males with soccer and tennis and in women with aerobic dance and fitness walking. CONCLUSION: In the Olomouc region there is a need to preserve and develop the conditions to perform PA. Due to the landscape in the Olomouc region and due to the popularity of cycling, we recommend focus on this type of PA.